Study of cytostatic and cytotoxic characteristics of modified peptide CDK4/6 inhibitors – functional analogs of p16INK4a (90-97) - V. K. Bozhenko; T. M. Kulinich; E. A. Kudinova; A. V. Ivanov; A. M. Shishkin; V. A. Solodkiy (Успехи молекулярной онкологии)
Background. Application of mathematical modeling for search for biologically active molecules is currently a promising scientific approach. Application of numerical algorithms for optimization of peptide sequences and molecular dynamics allowed to obtain modified peptide sequences that are functional analogs of the sequence of natural inhibitor of cyclin-dependent kinase 4/6 p16INK4a.The study objective is to establish biological characteristics of peptide sequences of CDK 4/6 inhibitors obtained using mathematical modeling.Materials and methods. The studies were performed in vitro using tumor cell lines (MCF-7, А549, SKOV-3, НСТ116). Apoptosis level, cell distribution per cell cycle stages, changes in Bcl-2 expression, changes in the level of phosphorylated pRb under the effect of the studied molecules were investigated using flow cytometry. Proliferation dynamics of cell populations were studied using RTCA iCELLIgence biosensor technology.Results. Peptide sequences obtained using mathematical modeling decrease the level of phosphorylated pRb, Bcl-2 expression when applied to actively proliferating cells. These proteins serve as molecular targets for the cyclin-dependent kinase 4/6–cyclin D complex, and changes in pRb and Bcl-2 levels might indicate inhibition of complex formation. Consequently, decreased proliferative activity and increased apoptosis were observed. Effectiveness of the peptide sequences depended on their molecular structure and type of the used cell line. Two (2) of the studied modified peptide sequences have higher antiproliferative and proapoptotic effect on tumor cells than native p16INK4a (90-97) sequence.Conclusion. Application of mathematical modeling for search and development of functionally active molecules allowed to create peptide sequences with stronger cyclin-dependent kinase inhibitor effect than p16INK4a, the native inhibitor CDK4/6.